2003
DOI: 10.1046/j.1442-9071.2003.00617.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Zeiss IOLMaster and applanation A‐scan ultrasound: biometry for intraocular lens calculation

Abstract: The IOLMaster provides an accurate axial length measurement and results in accurate intraocular lens power calculation based on the SRK/T formula. It is quick and easy to use and provides a non-contact technique with no risk of infection or corneal abrasion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
2
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(68 citation statements)
references
References 17 publications
3
62
2
1
Order By: Relevance
“…In a comparative study of 50 cataractous eyes, pre and postoperatively, Packer et al 23 found that 92% of them were within 0.50 D and 100% were within 1 D of the targeted refraction; IOL power was computed from the IOLMaster using the Holladay II formula. Two other studies 7,24 showed that a high percentage of patients (87 and 91%) assigned to IOLMaster biometry achieved targeted refraction of within 1 D, compared with about 80% in the applanation group. In another study, 25 the two figures were even reported to be as high as 96 and 93%, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…In a comparative study of 50 cataractous eyes, pre and postoperatively, Packer et al 23 found that 92% of them were within 0.50 D and 100% were within 1 D of the targeted refraction; IOL power was computed from the IOLMaster using the Holladay II formula. Two other studies 7,24 showed that a high percentage of patients (87 and 91%) assigned to IOLMaster biometry achieved targeted refraction of within 1 D, compared with about 80% in the applanation group. In another study, 25 the two figures were even reported to be as high as 96 and 93%, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…Axial length can easily and precisely be measured. [16][17][18] Several studies have shown a decrease of axial eye length with lowered intraocular pressure after trabeculectomy. [19][20][21][22] A recent study by Leydolt et al 23 measured the change of axial eye length after mechanically inducing intraocular pressure elevation.…”
Section: à3mentioning
confidence: 99%
“…Moreover, resolution and precision of partial coherence interferometry is known to be about 10 times better than that of ultrasound-based methods. 16,24 Recent studies using finite element modelling showed that the biomechanical properties of the corneoscleral shell profoundly affect the level of mechanical stress experienced by the optic nerve head (ONH). 27,28 Forces at the ONH have been shown to be up to 180 times IOP.…”
Section: Eyementioning
confidence: 99%
“…Partial coherence interferometry, by the IOL Master (Zeiss, Jena, Germany), has recently become available and is essentially technician independent [2]. In addition, the IOL Master provides a noncontact technique with no risk of infection or corneal abrasion [3]. The AL measured by the IOL Master (AL IOLM ) is more accurate and reproducible than that by US (AL US ) in a normal eye [4, 5] or in a pseudophakic eye [6].…”
Section: Introductionmentioning
confidence: 99%